Storage stability of mayonnaise packaged in soy protein isolate films incorporated with mango kernel extract - Maryam Adilah, Z.a.; Jamilah, B.; Nur Hanani, Z.a. (Elsevier, 2023)
Antioxidant films based on soy protein isolate (SPI) and mango kernel extract (MKE) were developed to lower the lipid oxidation of mayonnaise. Mayonnaise packaged in control films (SPI only) and antioxidant films (SPI+MKE films) were stored for 6 weeks and the analyses were conducted on every 1-week interval. SPI+MKE films successfully slowed down the total oxidation value (TOTOX) of mayonnaise up to 65% relative to the control films. The lipid oxidation analyses such as peroxide value, TBARS and anisidine value recorded 30%, 37% and 38% lower lipid oxidation values for samples in SPI+MKE films as compared to control films. In this research, the active packaging successfully prolongs the shelf life of mayonnaise without additives by up to 14 days storage.